2019
DOI: 10.1007/s00115-019-0735-1
|View full text |Cite
|
Sign up to set email alerts
|

Autoantikörper-assoziierte schizophreniforme Psychosen: Pathophysiologie, Diagnostik und Therapie

Abstract: Online teilnehmen 3 Punkte sammeln auf CME.SpringerMedizin.de Teilnahmemöglichkeiten Die Teilnahme an diesem zertifizierten Kurs ist für 12 Monate auf CME.SpringerMedizin.de möglich. Den genauen Teilnahmeschluss erfahren Sie dort. Teilnehmen können Sie:-als Abonnent dieser Fachzeitschrift,-als e.Med-Abonnent. Zertifizierung Diese Fortbildungseinheit ist zertifiziert von der Ärztekammer Nordrhein gemäß Kategorie D und damit auch für andere Ärztekammern anerkennungsfähig. Es werden 3 Punkte vergeben. Anerkennung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 43 publications
0
32
0
3
Order By: Relevance
“…The recommendations worked out here for Abs assessment and respective diagnostic and therapeutic consequences in schizophreniform psychoses were based on consensus from emerging clinical evidence rather than from systematic randomized studies as is the case with the present recommendations for diagnosis and treatment of AE [31]. Beyond, it should be recognized that indeed both well-established clinical terms (like encephalitis, encephalopathy, neuroinflammation) and newly proposed terms (such as AP, AE) are hardly exactly defined, thus for clinical use typically represent just clinical case definitions based on respective Table 3 The most important known autoantibodies that can be associated with symptoms of schizophreniform psychoses [9,15,31,34,36,37,38,48,63,71,79,81,82,84,85,90 limited and steadily emerging clinical consensus [6,12]. In addition, the possibility of underlying so far not identified new Abs is also limiting the whole issue.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The recommendations worked out here for Abs assessment and respective diagnostic and therapeutic consequences in schizophreniform psychoses were based on consensus from emerging clinical evidence rather than from systematic randomized studies as is the case with the present recommendations for diagnosis and treatment of AE [31]. Beyond, it should be recognized that indeed both well-established clinical terms (like encephalitis, encephalopathy, neuroinflammation) and newly proposed terms (such as AP, AE) are hardly exactly defined, thus for clinical use typically represent just clinical case definitions based on respective Table 3 The most important known autoantibodies that can be associated with symptoms of schizophreniform psychoses [9,15,31,34,36,37,38,48,63,71,79,81,82,84,85,90 limited and steadily emerging clinical consensus [6,12]. In addition, the possibility of underlying so far not identified new Abs is also limiting the whole issue.…”
Section: Limitationsmentioning
confidence: 99%
“…factors [81]. Large, genome-wide studies have identified over 100 distinct gene sites that contribute to the relative risk of psychotic symptoms [73].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Das limbische System stellt einen Prädilektionsort für Autoimmunenzephalitiden dar [33,34,35]. Man hat mittlerweile mehrere mit einer limbischen Enzephalitis assoziierte Zielproteine entdeckt (NMDA, AMPA, GA-BAb, LGI1, GAD65, Hu, Ma2 u.…”
Section: Autoimmunenzephalopathienunclassified
“…Der Verlauf gestaltet sich zumeist progredient, zum Teil fluktuierend, oft mit ausgeprägten vegetativen Symptomen. Im EEG können als "sensitivste, wenngleich wenig spezifische, apparative Methode" [34] Verlangsamungen und epilepsietypische Potentiale mit temporaler Lokalisation sowie die sogenannten extreme delta brush gefunden werden [37]. Der Liquor zeigt eine Pleozytose (< 100) in 60-80 % und einen erhöhten IgG-Index oder oligoklonale Banden in ca.…”
Section: Autoimmunenzephalopathienunclassified